Sustainability of the Global Water Supply: An Exploratory Study of International Managers' Perspectives - Rivas, Ronald M. (Archīum Ateneo, 2023)
Water risk, both in terms of the risk to human life related to such threats as water scarcity and the risk to business related to such challenges as mismanagement of a critical resource, is a topic of increasing interest and importance to policymakers worldwide. The problems associated with water risk are being tackled by international development organizations such as the United Nations and the Organization for Economic Co-operation and Development; by international business organizations such as the World Business Council for Sustainable Development and the World Resources Institute; and by international aid organizations such as Water.org and countless corporate foundations. There is no shortage of brainpower, passionate commitment, or money spent on finding solutions to a growing problem. However, the problems continue. This research effort’s premise is that solutions to problems around the sustainability of the water supply remain elusive because such considerations have not yet become part of the day-to-day problem-solving routine of managers across the hierarchy of business organizations. In this study, managers in Brazil and South Korea were surveyed on their perspectives on the factors in their external environments that held promise for improving the sustainability of the world’s water supply. Our analysis identifies stakeholders in the external environment with whom managers might build effective coalitions for addressing this critical issue.